2022
DOI: 10.3390/ijerph19148853
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence (IPV) in Military and Veteran Populations: A Systematic Review of Population-Based Surveys and Population Screening Studies

Abstract: Intimate partner violence (IPV) may be a major concern in military and veteran populations, and the aims of this systematic review were to (1) provide best available estimates of overall prevalence based on studies that are most representative of relevant populations, and (2) contextualise these via examination of IPV types, impacts, and context. An electronic search of PsycINFO, CINHAL, PubMed, and the Cochrane Library databases identified studies utilising population-based designs or population screening str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Absent from research on IPV during the COVID-19 pandemic are women veterans, whom experience high risk for IPV. 15,16 Women veterans also have greater trauma exposures than non-Veteran women. 17,18 Military sexual trauma (MST) and combat exposure are prevalent military-related experiences among women veterans.…”
mentioning
confidence: 99%
“…Absent from research on IPV during the COVID-19 pandemic are women veterans, whom experience high risk for IPV. 15,16 Women veterans also have greater trauma exposures than non-Veteran women. 17,18 Military sexual trauma (MST) and combat exposure are prevalent military-related experiences among women veterans.…”
mentioning
confidence: 99%
“…These findings are informing the scale-up of RISE in the VHA and may be helpful to other healthcare settings that desire to implement psychosocial counseling interventions for patients who experience IPV. In particular, IPV is a common social determinant of health among Veterans and there is a strong need for evidence-based interventions to be implemented in Veteran-specific settings [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, estimates of IPV victimization in both men and women, general and military populations are predicated on insufficiently described samples and carry interpretation challenges. Among women military personnel, published prevalence rates have ranged from 5% to 58% 7 . Wide ranges across any studies have probable contributors that include varied sampling, often with mixes of types of IPV exposure and mixes of veterans and/or active-duty participants.…”
Section: Prevalence Of Exposure To Ipv Victimization In Women and Its...mentioning
confidence: 99%
“…As further related to interpretive challenges, women as the recipients of IPV are of preeminent concern in women's health care, but interestingly, evidence from military populations has shown that both women and men perpetrate IPV and rates of victimization between them remain undifferentiated. In their meta-analysis of 31 population survey or screening studies across multiple countries (n = 26 from the United States) with veteran and/or active-duty male and female personnel reporting recent IPV perpetration or victimization (in the past year, past 6 months, past month, or within current relationship), Cowlishaw et al 7 indicated that about 13% (95% CI, 4.9%-29.0%) claimed recent perpetration and 21% (95% CI, 13.1%-31.1%) reported recent victimization (n = 14 studies), which is higher than in the general mixed gender population whereby ~6% reported past-year perpetration and ~5% reported past-year victimization. In the reviewed studies, no gender-related differences were detected for either perpetration or victimization.…”
Section: Prevalence Of Exposure To Ipv Victimization In Women and Its...mentioning
confidence: 99%
See 1 more Smart Citation